THE INTERNET OF THINGS AS A COMPONENT OF INDUSTRY 4.0: A PROJECT APPROACH - Dyavil, Artem; Nozdrina, Larysa (Socio-economic relations in the digital society, 2020)
The article describes the theoretical, methodological foundations of the formation of Industry 4.0 in the world and in Ukraine in particular. The state and global trends in the development of the Internet of Things as a component of the fourth industrial revolution are analyzed. The basics of the project approach to the implementation of the Internet of Things are highlighted, in particular, the concept of an IoT project and its place in the general classification of projects. The article discusses the classification of projects of the Internet of Things, as well as positive and negative factors for their implementation. The special importance of ensuring both the information (Security Projects) and the functional component (Projects Safety) of the security of IoT projects was emphasized, since their goal is to create a complex cyber-physical system for managing enterprises, smart cities, and so on. The article describes the IoT-project «DiRlG», which belongs to the Home Automation System class and is designed to automatically control a specific building in real-time. The proposed concept of an IoT project, which will be based on a monolithic-modular system, which allows plug and play additional systems (modules) in real time. The capabilities of the main module for controlling the smart home system are demonstrated. To implement the project was proposed to use the SCRUM framework of an agile project management methodology and Jira software. The business model and stakeholders of the project are presented. The article also presents the roadmap of the first phase of the DiRlG project and describes the main modules of the system and their functionality. Our proposed project IoT — «DiRlG» is a way to automatically control the entire building in real time. The product of the project is unique in that it will be easy to use. From an economic point of view, DiRlG will be able to design the building in such a way that all services will communicate with each other, and as a result will achieve the optimal level of response to any processes that take place in real time. Due to the optimal response to events, stability is achieved and the lifetime of the system is increased — because during the failure of one module, other related modules can start the process of emergency shutdown of a device